IMPLEMENTASI MODEL ROLE PLAYING UNTUK MENINGKATKAN MOTIVASI BELAJAR IPAS KELAS III SEKOLAH DASAR - Priska Nova Linda dasman; Qhori Lukfati Syah; Restu Aulia Mayori; Reva Amanda; Susi Ratna Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low learning motivation of third-grade students in Social Studies subjects, which was indicated by the lack of attention, active participation, curiosity, and persistence of students during the learning process. This condition was caused by the use of conventional learning models that were still teacher-centered, making students passive and easily bored. This study aimed to determine the implementation of the roleplaying learning model in improving the Social Studies learning motivation of third-grade elementary school students. The research method used was Classroom Action Research (CAR), which was conducted in two cycles, namely cycle I and cycle II. Each cycle consisted of planning, action, observation, and reflection stages. The results showed that the implementation of the role playing learning model was able to gradually improve students’ learning motivation. In the pre-cycle stage, students’ learning motivation reached 50% and was categorized as low. After the implementation of the role playing model in cycle I, learning motivation increased to 65% with a sufficient category, and in cycle II it significantly increased to 85% with a good category. Improvements also occurred in all indicators of learning motivation, including attention to the material, active participation, curiosity, and learning persistence. Therefore, the role playing learning model is effective in improving the Social Studies learning motivation of third-grade elementary school students.